Association of altitude and frailty in Chinese older adults: using a cumulative frailty index model - Dong, Yongfei; Ma, Hongmei; Sun, Hao; Li, Yuemei; Li, Xiaofang; Pan, Shiqin; Li, Caixia; Liu, Songbai; Tang, Zaixiang; Li, Lirong (Frontiers in Public Health, 2024)
Objective: The population is aging exponentially and the resulting frailty is becoming increasingly evident. We aimed to explore the association between altitude and frailty, and to identify associated factors for frailty.Methods: This is a community-based cross-sectional survey. 1298 participants aged ≥ 60 years from three different altitudes were included in the study. To quantify frailty, we constructed a frailty index (FI) and a frailty score (FS). The FI was divided into nonfrailty, prefrailty, and frailty. The Odds Ratios and confidence intervals (ORs, 95%CIs) were used to evaluate the association between altitude and FI and FS in multivariate ordinal logistic regression and linear regression.Results: There were 560 (53.1%) participants in the prefrailty and 488 (37.6%) in the frailty group. The FS increased with higher altitude (P for trend < 0.001). Multivariate ordinal logistic regression analysis revealed an association between altitude and frailty, OR = 1.91 (95% CI: 1.38-2.64) in mid-high altitude and 2.49 (95% CI:1.40-4.45) in high altitude. The same trend of association was found in the univariate analysis. The FS increased by 1.69 (95% CI: 0.78-2.60) at mid-high altitude and 3.24 (95%CI:1.66-4.81) at high altitude compared to medium altitude.The study indicates that high altitude exposure is an associated factor for frailty in older adults. This association become stronger with higher altitudes. As a result, it is essential to conduct early frailty screening for residents living at high altitudes.